2016
DOI: 10.1097/bot.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Healing Time and Complications in Operatively Treated Atypical Femur Fractures Associated With Bisphosphonate Use

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 18 publications
2
43
0
1
Order By: Relevance
“…Similarly, Prasarn and colleagues, in a study in which the outcomes of intramedullary nailing of atypical femoral fractures were compared between patients receiving bisphosphonates and those without a history of bisphosphonate exposure, found that patients receiving bisphosphonates had a significantly higher rate of intraoperative fracture, malunion, nonunion, implant failure, and periprosthetic fracture 41 . In a more recent multicenter series, the revision rate was 9% among patients with complete displaced atypical femoral fractures, with 20% of the patients having fracture-healing after six months 42 . Conversely, Ha et al reported complete union of ten atypical femoral fractures after initial internal fixation 43 .…”
Section: Treatmentmentioning
confidence: 98%
“…Similarly, Prasarn and colleagues, in a study in which the outcomes of intramedullary nailing of atypical femoral fractures were compared between patients receiving bisphosphonates and those without a history of bisphosphonate exposure, found that patients receiving bisphosphonates had a significantly higher rate of intraoperative fracture, malunion, nonunion, implant failure, and periprosthetic fracture 41 . In a more recent multicenter series, the revision rate was 9% among patients with complete displaced atypical femoral fractures, with 20% of the patients having fracture-healing after six months 42 . Conversely, Ha et al reported complete union of ten atypical femoral fractures after initial internal fixation 43 .…”
Section: Treatmentmentioning
confidence: 98%
“…The authors speculate that for mechanical reasons, AFFs could be more common in more physically active elderly patients and/or AFFs could have a more benign course in terms of complications. These are valid considerations, though the tendency for AFFs to be bilateral and to heal more slowly would seem to contradict at least the latter notion …”
Section: Simple Tabulation Of Femur and Hip Fractures In Sweden And Ementioning
confidence: 99%
“…These are valid considerations, though the tendency for AFFs to be bilateral and to heal more slowly would seem to contradict at least the latter notion. (5) The existing evidence base is fairly consistent in terms of excess mortality after most if not all osteoporotic fractures, with higher relative risk in younger patients and in men. National differences in post-fracture mortality can be pronounced even within Europe, (6) but mortality after osteoporotic fractures in Sweden has been well characterized thanks to the availability of good X-ray records and national mortality data.…”
mentioning
confidence: 91%
“…[8] Radiologically, it can be seen that these fractures start from the lateral cortex and have transverseoblique orientation may cause spike formation in the medial cortex, or cortical thickening and periosteal reaction. [8,9] surgery rates [10,11] because of their rarity, the number of comprehensive studies on BP related AFF in the literature is limited and information on the outcome of these fractures is insufficient, which remained under-researched. The present study aims to report the radiological and clinical outcomes of the patients who were operated with the diagnosis of BP related AFF.…”
Section: Introductionmentioning
confidence: 99%